VD_FINDINFO 223 vom 3. Dezember 2024 - VD Tribunal cantonal (2024)
PRÉSOMPTION D'INNOCENCE, FAUX DANS LES CERTIFICATS, SURSIS À L'EXÉCUTION DE LA PEINE | 252 CP, 42 al. 1 CP, 10 CPP (CH), 118 al. 1 LEI